ANALYSIS OF THE EFFICACY OF 430 NM LED IN REDUCING BACTERIAL CONTAMINATION IN RENAL SCAFFOLD SLICES - Rios, Ana Laura Ferreira; Moura, Ricardo Silva; Silva, Bruna Martins Rodrigues; Oliveira, Rodrigo Franco de; Oliveira, Deise Aparecida de Almeida Pires- (CIPEEX, 2025)
Objective: This study aims to review the existing literature on the development and applications of 430 nm LED in bacterial inactivation in renal tissue scaffold slices, emphasizing its potential for clinical applicability. Methodology: A literature search was conducted in the PubMed database in August 2024, using the descriptors "phototherapy," "urology," "sterilization," or "bacterial inactivation," according to DeCS/BVS. Only original articles published between 2020 and 2024, available in English or Portuguese and open access, that directly addressed the topic were included. Non-original studies that dealt only with LEDs of wavelengths other than blue light were excluded. Results: The LED has proven to be a promising alternative to the widespread use of antibiotics, which contributes to bacterial resistance. However, challenges remain. Conclusion: The use of LED technology has shown to be effective, but further research is required to refine and optimize its application.